ANTI-IL-6 ANTIBODY TREATMENT BUT NOT IL-6 KNOCKOUT IMPROVES INTESTINAL BARRIER FUNCTION AND REDUCES INFLAMMATION FOLLOWING BINGE ETHANOL EXPOSURE AND BURN INJURY - Zahs, Anita (2013)
IL-6 is an inflammatory cytokine known to be elevated in chronic diseases and following insults such as trauma and infection. While necessary for the development of B cells and Th17 cells, IL-6, at elevated levels, can also cause tissue damage and lead to a rise in inflammation. Previous work in our laboratory has shown that IL-6 is increased both systemically as well as in multiple organ systems including the ileum following ethanol exposure and burn injury. As this combined insult causes elevated intestinal morphological damage, tight junction protein localization alterations, and phospho myosin light chain (pMLC) levels, we sought to determine the role of IL-6 in these intestinal responses using a model of binge ethanol exposure and burn injury. IL-6 antibody treatment after the combined insult reduced morphological changes in the ileum, bacterial translocation, and pMLC levels relative to either injury alone. ZO-1 and occludin localization was also re-established in wild type mice given IL-6 antibody after ethanol and burn. IL-6 knockout mice given ethanol and burn injury also had reduced intestinal damage; however, no changes in bacterial translocation or tight junction protein localization were observed as compared to similarly treated wild type mice. These data suggest that IL-6 may have a role in intestinal tissue damage observed following the combined insult of binge ethanol exposure and burn injury although complete loss of IL-6 does not appear to be beneficial in this model. Modulation of IL-6 may present a new option for preventing intestinal damage and associated inflammation following a combined insult of ethanol exposure and burn injury.